Flat Earth: From a persistent myth to a scientific metaphor - I. V. Trotsuk (RUDN journal of Sociology, 2025)
The article is an essay based on two recently published in Russian popular science books, both mentioning the flat Earth in their titles (although one only in its Russian edition) but for solving different research problems. The first book by V. Giacomotto-Charra and S. Nony The Flat Earth : Genealogy of a False Idea reconstructs the myth about the origin of the flat Earth myth and could not do without detailed characteristics of the essence and factors of the formation of the flat-earthers movement. The second book by D. McRaney How Minds Change: The Surprising Science of Belief, Opinion, and Persuasion mentions this movement only on the very last pages (in the epilogue) due to the use of the concept of the flat Earth as a kind of scientific metaphor implying a multitude of different factors of the spread of unscientific and pseudoscientific ideas in the contemporary world which we prefer to perceive as a stronghold of scientific progress and a rational worldview. The article briefly summarizes the content of two books to confirm the proposed perspective of the perception of “flat-earthism” and provides “expert assessments” illustrating and complementing this perspective.